2022
DOI: 10.21203/rs.3.rs-1350094/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipstick on a pig: Understanding efforts to redesign audit and feedback reports for primary care.

Abstract: Background: In Ontario, Canada, a government agency known as Ontario Health is responsible for making audit and feedback reports available to all family physicians. The confidential report provides summary data on three key areas of practice: safe prescribing, cancer screening, and diabetes management. This report was redesigned to improve its usability and the objective of this study was to explore how the redesign was perceived. Methods: We conducted qualitative semi-structured interviews with family physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…We observed that participants without prior use of A&F were more sceptical of A&F as a tool than participants who had used A&F prior to the focus group. In line with previous research, this suggests being unknown with A&F, makes it unloved 18 19. While A&F has been used as a QI intervention in healthcare for years, studies consistently report physicians’ incapability to interpret population-level feedback 19–22.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that participants without prior use of A&F were more sceptical of A&F as a tool than participants who had used A&F prior to the focus group. In line with previous research, this suggests being unknown with A&F, makes it unloved 18 19. While A&F has been used as a QI intervention in healthcare for years, studies consistently report physicians’ incapability to interpret population-level feedback 19–22.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, even when the quality of the feedback itself is sufficient, recipients may still need education on how to interpret and translate A&F into change. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Experts state that the optimal design of A&F likely depends on recipient factors and context, but it is yet unclear which thresholds exists for quality of feedback to be ‘sufficient’ to contribute to motivation to change6 Furthermore, Desveaux et al 35 describe that ‘A&F may not be translated into actual change, due to incapability of participants to interpret A&F in an actionable way’. Thus, even when the quality of the feedback itself is sufficient, recipients may still need education on how to interpret and translate A&F into change 41…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations